The wreck of the Dutch man o' war, Amsterdam, in December 1817 on the Eastern Cape coast of Southern Africa: an elucidation of the literary and material remains with an annotated translation of the Journal of Captain Hermanus Hofmeijer (1814-1818) - Bennie, Jennifer Shirley (Rhodes University, Faculty of Humanities, Department of History, 1998)
This study endeavours to elucidate the journal of Captain Hermanus Hofmeijer of the Dutch man 0' war, Amsterdam, which has been transcribed from the original script, translated from Dutch into English and interpreted from a contemporary viewpoint. It offers an opportunity to evaluate a unique primary historical document which records an important historical event. An attempt has been made to contextualise the incident in the light of the early history of the Dutch people. The contribution of the Dutch East India Company (VaC) to the trade and commerce of the Netherlands during the 17th and 18th centuries has been assessed together with the shipbuilding techniques that served to make the Dutch a major seafaring nation. The significance of Texel and Nieuwediep has been examined and the sea route and navigational instruments placed in perspective. The voyage has been analysed in some detail. The background of Captain Hermanus Hofmeijer has proved especially interesting. Although he pursued his career with the Dutch Navy, he was born and spent his early years in Cape Town, South Africa. The time spent by the Amsterdam in Batavia, Samaraog and Sourabaya gives an insight into the Dutch possessions overseas. The return voyage, storms and ultimate grounding are of special interest as Hofmeijer records the journey and events on a daily basis. The impact and significance of 217 extra people in the Eastern Cape area did not go unnoticed, and although the event was not well documented, an attempt at some contextualisation has been made. Finally a short overview of maritime archaeology in South Africa and its significance as a relatively new discipline has been included. The study of the material remains of the wreck of the Amsterdam has resulted in a new understanding of wooden ships built in the early 19th century.
Keywords: Amsterdam (Steamship); Shipwrecks -- South Africa; Underwater archaeology; Nederlandsche Oost-Indische Compagnie; Hofmeijer, Hermanus, 1721-1805--Diaries; Voyages and travels -- History -- 18th century